Resource Management and Health Service Delivery in Rukungiri Municipality: A Case Study of Rwamahwa Health Center IV. - Ndyamuhak,i Faith (Kabale University, 2023)
The study examined resource management and health service delivery in Rukungiri Municipality a case study of Rwamahwa Health Center IV. The objectives of the study were; to establish the influence of material resource management on health service delivery at Rwamahwa Health Center IV Rukungiri Municipality, to determine the influence of human resource management on health service delivery at Rwamahwa Health Center IV, Rukungiri Municipality, and to examine the relationship between financial resources management and health service delivery at Rwamahwa health center IV, Rukungiri Municipality. The study employed a descriptive research design and data was collected using questionnaires and interviews. The study findings on the influence of material resource management on health service delivery at Rwamahwa Health Center IV Rukungiri Municipality were; that the health center has an adequate stock of drugs and medicines which ease service delivery, the health center has all the basic equipment and facilities in place to ensure better service delivery, the health equipments are well maintained to use provision of services and the health centre has a budget for maintenance to ensure that service delivery is to the desired standards. The study findings on the influence of human resource management on health service delivery at Rwamahwa Health Center IV, Rukungiri Municipality were; the health center has all staffing gaps filled which helps to ensure better service delivery, the health center has a medical doctor in place who delivers services promptly, health staff is facilitated to perform their tasks hence better service delivery in the organization, recruitment of health staff is on merit which leads to better provision of services, and deployment of health staff is on merit which leads to better delivery of services. The study findings on the relationship between financial resources management and health service delivery at Rwamahwa Health Center IV, Rukungiri Municipality were; the health centre has a budget in place which helps to procure the required products for effective service delivery, the budget is drawn based on stakeholders' priorities which helps all patients to have equal access to health services, the health center carries out monthly cash reconciliations to ensure timely service delivery, political leaders can easily access information from departments which helps to identify lope holes to service delivery and financial resources management helps to cater for infant which leads to their low rate of mortality. The study recommended that the health centers should ensure that they procure the basic equipment and facilities to ensure that they can be able to provide better services to the intended beneficiaries, health centers should always adhere to and follow their budgets so that they can be able to achieve their intended goals for better service delivery to their clients and there is a need to ensure that the right procedures for recruitment of the employees are followed so that competent staff can be employed which can lead to improved and better service delivery.